Quantum Walk-Based Vehicle Routing Optimisation - Bennett, T.; Matwiejew, E.; Marsh, S.; Wang, J. B. (Frontiers in Physics, 2021)
This paper demonstrates the applicability of the Quantum Walk-based Optimisation Algorithm (QWOA) to the Capacitated Vehicle Routing Problem (CVRP). Efficient algorithms are developed for the indexing and unindexing of the solution space and for implementing the required alternating phase-walk unitaries, which are the core components of QWOA. Results of numerical simulation demonstrate that the QWOA is capable of producing convergence to near-optimal solutions for a randomly generated 8 location CVRP. Preparation of the amplified quantum state in this example problem is demonstrated to produce high-quality solutions, which are more optimal than expected from classical random sampling of equivalent computational effort.